Atypical Mycobacterial Infection: An Achilles heel for Clinician - Ahasan, HAM Nazmul (Bangladesh Journal of Medicine, 2023)
Atypical mycobacteria or nontuberculous mycobacteria are organisms that cause various diseases such as skin and soft tissue infection, lymphadenitis, pulmonary infection, disseminated infection, and a wide range of more rarely encountered infections. The mycobacteria that most commonly cause this condition are most commonly found in the soil, indoor and outdoor water sources, and are recognized to colonize poorly sanitized medical equipment. Atypical mycobacteria most commonly infect young children, immunocompromised individuals, individuals with indwelling medical equipment, and those who have recently undergone surgical or non-surgical procedures. These bacteria can be further categorized into slow and rapidly growing organisms and grouped by the organ systems they commonly affect. Due to their morphology and growth patterns, atypical mycobacteria are difficult to identify on diagnostic testing. Treatment often requires extended courses of combination antibiotic therapy, frequently with surgical intervention. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 184